2020
DOI: 10.1007/s00246-020-02509-6
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Echocardiographic Dimension Indices: Important Predictors of Postnatal Coarctation

Abstract: The aim of the study is to identify reliable quantitative fetal echocardiographic predictors for postnatal development of coarctation (CoA). In this retrospective study, we included 65 fetuses with a prenatally suspected, isolated CoA, born 2010–2018. Dimensions of the cardiac structures, aortic, and ductal arches expressed as ratios and Z-scores were analyzed in relation to outcome. Fetuses that developed CoA postnatally (34%) exhibited significantly smaller Z-scores of left cardiac structures from the mitral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 29 publications
8
24
0
2
Order By: Relevance
“…In previous studies [20], it has been observed that the peak transaortic velocity is significantly greater in those fetuses in which CoAo is confirmed after birth and require surgery. In the same way, a bidirectional or left-right interatrial shunt and a bidirectional/retrograde flow at the aortic arch have been reported more frequently in fetuses with CoAo, but with a low specificity [33]. However, as in our series, other studies did not observe differences for functional parameters (flow at the aortic arch and FO) between CoAo and no CoAo fetuses [18,20,24].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In previous studies [20], it has been observed that the peak transaortic velocity is significantly greater in those fetuses in which CoAo is confirmed after birth and require surgery. In the same way, a bidirectional or left-right interatrial shunt and a bidirectional/retrograde flow at the aortic arch have been reported more frequently in fetuses with CoAo, but with a low specificity [33]. However, as in our series, other studies did not observe differences for functional parameters (flow at the aortic arch and FO) between CoAo and no CoAo fetuses [18,20,24].…”
Section: Discussionsupporting
confidence: 83%
“…However, as in our series, other studies did not observe differences for functional parameters (flow at the aortic arch and FO) between CoAo and no CoAo fetuses [18,20,24]. We also did not find differences for PLSVC according to postanal outcome (CoAo vs. no CoAo), similarly to other groups [18,22,24,25,33]. Nevertheless, Morgan et al [20] found more cases of PLSVC in fetuses with CoAo compared to normal cases, although in the multivariate analysis, it was not statistically significant.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations